Inhibition of Intimal Thickening By PRH (Proline-Rich Homeodomain) in Mice. Issue 3 (26th January 2023) - Reolizo, Lien M.; Williams, Helen; Wadey, Kerry; Frankow, Aleksandra; Li, Ze; Gaston, Kevin; Jayaraman, Padma-Sheela; Johnson, Jason L.; George, Sarah J.
Abstract : Background: Late vein graft failure is caused by intimal thickening resulting from endothelial cell (EC) damage and inflammation which promotes vascular smooth muscle cell (VSMC) dedifferentiation, migration, and proliferation. Nonphosphorylatable PRH (proline-rich homeodomain) S163C:S177C offers enhanced stability and sustained antimitotic effect. Therefore, we investigated whether adenovirus-delivered PRH S163C:S177C protein attenuates intimal thickening via VSMC phenotype modification without detrimental effects on ECs. Methods: PRH S163C:S177C was expressed in vitro (human saphenous vein–VSMCs and human saphenous vein–ECs) and in vivo (ligated mouse carotid arteries) by adenoviruses. Proliferation, migration, and apoptosis were quantified and phenotype was assessed using Western blotting for contractile filament proteins and collagen gel contraction. EC inflammation was quantified using VCAM (vascular cell adhesion protein)-1, ICAM (intercellular adhesion molecule)-1, interleukin-6, and monocyte chemotactic factor-1 measurement and monocyte adhesion. Next Generation Sequencing was utilized to identify novel downstream mediators of PRH action and these and intimal thickening were investigated in vivo. Results: PRH S163C:S177C inhibited proliferation, migration, and apoptosis and promoted contractile phenotype (enhanced contractile filament proteins and collagen gel contraction) compared with virus control in human saphenous vein–VSMCs. PRH S163C:S177C expression in human saphenous vein–ECs significantly reduced apoptosis, without affecting cell proliferation and migration, while reducing TNF (tumor necrosis factor)-α–induced VCAM-1 and ICAM-1 and monocyte adhesion and suppressing interleukin-6 and monocyte chemotactic factor-1 protein levels. PRH S163C:S177C expression in ligated murine carotid arteries significantly impaired carotid artery ligation-induced neointimal proliferation and thickening without reducing endothelial coverage. Next Generation Sequencing revealed STAT-1 (signal transducer and activator of transcription 1) and HDAC-9 (histone deacetylase 9) as mediators of PRH action and was supported by in vitro and in vivo analyses. Conclusions: We observed PRH S163C:S177C attenuated VSMC proliferation, and migration and enhanced VSMC differentiation at least in part via STAT-1 and HDAC-9 signaling while promoting endothelial repair and anti-inflammatory properties. These findings highlight the potential for PRH S163C:S177C to preserve endothelial function whilst suppressing intimal thickening, and reducing late vein graft failure.